Studies on bovine infertility at the Agricultural Research Station, (Legon) over half a decade (1972-77) - Osmana, S.T. (1979)
Reproductive performances of Gudali, West African Shorthorn, N'Dama and their crosses with Friesian and Jersey cattle were investigated. Five years reproduction data of the herd at Legon Agricultural Research Station, Ghana were analysed to determine the causes, incidence and pattern of male and female infertility. Discussions and data on compared relative merits, with respect to reproductivity and infertility of purelines and their crosses reported.